Keabsahan Jual Beli Tanah Tanpa Melampirkan Kartu BPJS Kesehatan: Post Inpres Nomor 1 Tahun 2022 - Afifah, Nur; Purwaningsih, Sri Budi (Indonesian Journal Publisher, 2023)
Everyone needs land, not only in life, at the time of death humans also need land. Along with the increasing number of people, the need for land is increasing for housing as well as for growth and development, socio-culture, and technology. The purpose of this paper is to determine the legitimacy of buying and selling land without attaching a BPJS Health Card: Post Presidential Instruction 1 Year 2022. This type of research is normative legal research, namely by using statutory regulations. The emphasis of normative juridical research in accordance with the distinctive character of legal scholarship lies in the study of law or legal studies of positive law. The conclusion is that buying and selling without attaching a BPJS Health card according to Government Regulation Number 24 of 1997 is carried out before the PPAT with a Sale and Purchase Deed, and is proven by a certificate. With the Presidential Instruction number 1 of 2022 which instructs that the process of transferring land rights or buying and selling must attach a BPJS Health card and be an active participant in the National Health Insurance program, while referring to the hierarchy of legislation Government Regulations have a higher position than presidential instructions by Therefore, the process of transferring land rights or buying and selling is considered valid without attaching a BPJS Health card. This proves that the Presidential Instruction has not yet been carried out optimally.